Answer:
Option The product of [tex](-x+4)(x^2+3x-3)[/tex] is
[tex]-x^3+x^2+15x-12[/tex] is correct.
That is [tex](-x+4)(x^2+3x-3)=-x^3+x^2+15x-12[/tex]
Step-by-step explanation:
Given expression is [tex](-x+4)(x^2+3x-3)[/tex]
To find the product of the given expression :
[tex](-x+4)(x^2+3x-3)[/tex]
( By using the distributive property each term in the factor is multiplied by each term in the another factor )
[tex]=[-x(x^2)+(-x)(3x)+(-x)(-3)]+[4(x^2)+4(3x)+4(-3)][/tex]
[tex]=-x^3-3x^2+3x+4x^2+12x-12[/tex] ( adding the like terms )
[tex]=-x^3+x^2+15x-12[/tex]
Therefore [tex](-x+4)(x^2+3x-3)=-x^3+x^2+15x-12[/tex]
Therefore Option The product of
[tex](-x+4)(x^2+3x-3)[/tex] is [tex]-x^3+x^2+15x-12[/tex] is correct.
That is [tex](-x+4)(x^2+3x-3)=-x^3+x^2+15x-12[/tex]